Mixed volatility in a single device: memristive non-volatile and threshold switching in SmNiO3/BaTiO3 devices - Hamming-Green, Ruben; Van den Broek, Marcel; Bégon-Lours, Laura; Noheda, Beatriz (Frontiers in Materials, 2024)
Analog neuromorphic circuits use a range of volatile and nonvolatile memristive effects to mimic the functionalities of neurons and synapses. Creating devices with combined effects is an important avenue to reduce the footprint and power consumption of neuromorphic circuits. In this work, we present an epitaxial SmNiO 3 /BaTiO 3 electrical device, which displays nonvolatile memristive switching that either allows or blocks access to a volatile threshold switching regime. This behavior arises from the coupling of the BaTiO 3 ferroelectric polarization to the SmNiO 3 metal-insulator transition (MIT): The polarization in the BaTiO 3 layer, in contact with the SmNiO 3 layer, modifies the device resistance continuously in a controllable, nonvolatile manner.Additionally, the polarization state varies the threshold voltage at which the Joule heating-driven insulator-to-metal phase transition occurs in the nickelate, which results in a negative differential resistance curve and produces a sharp, volatile threshold switch. Reliable current oscillations, with stable frequencies, large amplitude and requiring a relatively low driving voltage are demonstrated when the device is placed in a Pearson-Anson-like circuit.